Effects of the fractal structure and size distribution of flocs on the removal of particulate matter - de Oliveira, André Luiz [UNESP]; Moreno, Pamela [UNESP]; da Silva, Pedro Augusto Grava [UNESP]; De Julio, Marcelo; Moruzzi, Rodrigo Braga [UNESP] (Elsevier, 2016)
This study sought to evaluate the effect of form and particle size distribution of formed flocs during flocculation on the removal of particulate matter (PM) by settling. The understanding of the intrinsic processes of water treatment is fundamental for the improvement of these processes, and this understanding is often limited by the use of indirect measurements. For this reason, this study evaluated the relationships among the morphology, particle size distribution (PSD), and particle volume distribution of flocs formed with mean flocculation velocity gradients (Gf) from 20 to 60 s−1 and settling velocities from 0.5 to 5.0 cm s−1 at flocculation times (Tf) from 10 to 60 min. A correlation analysis of all of the parameters was performed to identify the most significant direct measurement for characterizing the removal of PM. Strong correlations among parameters were observed when considering the variation with Gf for a given Tf, and moderate correlations were observed when considering the variation with Tf for a given Gf. The strong correlations that resulted from the alteration of Gf were a consequence of the significant changes in the morphological characteristics, PSD, and PVD of the flocs. The lower strengths of the correlations with the variation in Tf can be explained by the rapid attainment of the equilibrium steady-state between aggregation and disaggregation forces.
Keywords: Morphology; Particle size distribution; Particle volume distribution; Particulate matter; Settling